Antara Qanun dan Fiqh Jinayat: Analisis Terhadap Sanksi Hukum Bagi Pelaku Zina di Aceh - Diana, Isna; Bahri, Anfal (Program Pascasarjana IAIN Langsa, 2024)
This study examines the dynamics of religiously-based marriages and divorces across several nations, including Indonesia, Tunisia, Turkey, the United States, and the United Kingdom. The study is driven by the varied methodologies about marriage and divorce, influenced by a confluence of statutory regulations, cultural customs, and religious tenets. The primary concern is how these nations manage the multiplicity of religious traditions while upholding justice and safeguarding individual rights. The study seeks to analyze the regulation of religious marriages and divorces by legal systems in various countries and to pinpoint best practices that could inform the reform of marriage laws in Indonesia. The research utilizes a literature review methodology to assess secondary data from books, research reports, and legal laws in the chosen nations. We employ a descriptive normative methodology to deliver an extensive investigation of the interaction of law, culture, and religion concerning marriage and divorce. The findings indicate that certain countries have effectively delineated the functions of religion and the state in the governance of marriage and divorce while preserving religious values. These regulations emphasize justice, encompassing the safeguarding of individual rights in divorce procedures, the fair allocation of assets, and the welfare of children. This study emphasizes the necessity of enacting legislation that honors cultural and religious diversity while guaranteeing equal protection for all individuals. This research provides valuable insights for establishing an inclusive and equitable marriage law system in Indonesia.